Adaptive Strategies for Dynamic Pricing Agents - Ramezani, S.; Bosman, P. A. N.; La Poutre, H. (2011 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology, 2011)
Dynamic Pricing (DyP) is a form of Revenue Management in which the price of a (usually) perishable good is changed over time to increase revenue. It is an effective method that has become even more relevant and useful with the emergence of Internet firms and the possibility of readily and frequently updating prices. In this paper a new approach to DyP is presented. We design an adaptive dynamic pricing strategy and optimize its parameters with an Evolutionary Algorithm (EA) offline, while the strategy can deal with stochastic market dynamics quickly online. We design the adaptive heuristic dynamic pricing strategy in a duopoly where each firm has a finite inventory of a single type of good. We consider two cases, one in which the average of a customer population's stochastic valuation for each of the goods is constant throughout the selling horizon and one in which the average customer valuation for each good is changed according to a random Brownian motion. We also design an agent-based software framework for simulating various dynamic pricing strategies in agent-based marketplaces with multiple firms in a bounded time horizon. We use an EA to optimize the parameters of the pricing strategy in each of the settings and compare our strategy with other strategies from the literature. We also perform sensitivity analysis and show that the optimized strategy works well even when used in settings with varied demand functions.